2014
DOI: 10.1063/1.4865377
|View full text |Cite
|
Sign up to set email alerts
|

Design of sub-1g microelectromechanical systems accelerometers

Abstract: This paper presents a design of microelectromechanical systems (MEMS) accelerometers for sensing sub-1g (g = 9.8 m/s2) acceleration. The accelerometer has a high-density proof mass to suppress the Brownian noise that dominates the output noise of the sensor. The low-temperature (<400 °C) process enables to integrate the accelerometer on the sensing complementary metal-oxide semiconductor circuit by electroplating of gold; a proof mass of 1020 μm × 1020 μm in area with the thickness of 12 μm has been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 18 publications
(15 reference statements)
1
64
0
Order By: Relevance
“…Fig. 8 schematizes the sub-1mG MEMS accelerometer [6,7]. The proof-mass is shifted by an acceleration input, thereby changing the capacitance between the proof-mass and the fixed electrode.…”
Section: Design and Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 8 schematizes the sub-1mG MEMS accelerometer [6,7]. The proof-mass is shifted by an acceleration input, thereby changing the capacitance between the proof-mass and the fixed electrode.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…Next, the capacitance-frequency characteristics were investigated using an LCR meter (IM3533-01, HIOKI E.E. Corp.), and the B n was evaluated from an analytical model [6]. The values of resonant frequency f res and the quality factor Q were 324 Hz and 2.15, respectively.…”
Section: Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make gold promising materials to be used as structure materials in micro-electro-mechanical systems (MEMS) devices. Yamane et al reported that the sensitivity of MEMS accelerometers using gold-based components would be higher when compared with the conventional silicon-based components [1][2][3] . The high sensitivity is mostly contributed by the much higher density of gold (19.30 g/cm 3 at 298 K) than silicon (2.33 g/ cm 3 at 298 K).…”
Section: Introductionmentioning
confidence: 99%
“…6 However, MEMS sensors for geophysical applications are emerging in the past two decades. MEMS seismic-grade accelerometers [7][8][9] have been developed to determine the surface seismic waves for either monitoring earthquakes or subsurface imaging oil exploration using the seismic reflection method, 10 including the 0.2 ng/ ffiffiffiffiffiffi Hz p short-period seismometer 11,12 recently developed in our group as a contribution to NASA's InSight Mars mission. There are also several reported MEMS angular accelerometers.…”
mentioning
confidence: 99%